Perceptions and Attitudes towards Manual and Online Catalogues among Undergraduate Students in Some Selected University Libraries in North Central, Nigeria - Bakare, Abdullahi A.; Ogochukwu, Nnajiofor (Ghana Library Journal, 2022)
This study examined perceptions and attitudes towards the uses of manual and automated catalogues among undergraduate students with a focus on three selected university libraries in North Central Nigeria, namely the University of Abuja Library, Abuja, Federal University of Technology Minna Library, Niger State and Kwara State University Library, Malete. The research design used in this study is a descriptive survey. The research population comprises the total number of undergraduate students registered with each of the libraries of the three selected universities in North Central, Nigeria. The University of Abuja Library had two thousand and seventeen (2,017) registered users, Federal University of Technology Minna, Library had two thousand four hundred and forty (2,440), and Kwara State University Malete library had four thousand eight hundred and twenty-four (4,824). This brings the total number of undergraduate library users registered with the three university libraries to 9,281. The sample size for the study was established using the random sampling table published by Israel in 1992. The table provided 200 for a population of 10,000 at ±7% Precision level and 95% confidence level. Therefore, 200 respondents were selected randomly which represent a cross-section of the population in each of the three selected universities in North Central. The instrument used to collect data was a structurally designed questionnaire. To ensure clarity of expressions and appropriateness of language used, the instrument went through face validation from some lecturers in library and information science in the selected universities. Reliability Test measurement yielded a value of 0.71 for Cronbach’s Alpha. A total number of two hundred (200) copies of the questionnaire were distributed randomly to the selected samples from the three selected institutions. Out of this, one hundred and twenty (120) copies, forty from each university library, were successfully filled, retrieved and found usable for the analysis, giving a response rate of 60%. The data generated from the questionnaire were analysed using descriptive statistics. Results were then presented in tabular forms and charts using simple percentages and frequency counts to facilitate a better understanding of the proportions in terms of particular responses. The study concluded that undergraduate students in the three selected university libraries prefer OPAC over the card catalogue; and that despite the availability of the OPAC many students still patronized the card catalogue, which means that in terms of patronage the gap between the OPAC and card catalogue is not that much. A periodic user education program for undergraduate students should be organized by the library management. This will give them the knowledge and abilities they need to find books and other information resources in the library using the card catalogue and OPAC as an effective searching tool.